Estrutura e composição em espécies da comunidade zooplanctônica de lagoas naturais da região de Lagoa Santa, Minas Gerais - Mirla Mayara de Castro Claro Gomes (2013)
Karstic enviroments, due to the soil features, are fragile and susceptible to contaminants, which make them unique. Aggravated by these features, lakes of the karstic region of Lagoa Santa Environmental Protected Area (MG) suffer from urbanization impacts. This study aimed to characterize the structure of the zooplankton community of natural, urban, tropical karstic lakes (Olhos dÁgua, Confins, Sumidouro, Mares), and to evaluate the factors that influence their diversity and structure. In order to do so, zooplankton and water samples were obtained from these lakes located within protected area (APA Carste Lagoa Santa- MG) in two seasons (rainy and dry) in two consecutive years (2009 and 2010) and from two sampling sites (limnetic and littoral zone). Furthermore, 8 diversity metrics were applied (absolute richness, rarefied richness, evenness Evar, Simpson diversity together with 4 taxonomic distinctness metrics: Delta, Delta*, Delta+ and Lambda+) to compare the lakes. In Lake Mares, the richer and more even and with high taxonomic distinctness, environmental heterogeneity (presence of macrophytes) can be considered an important factor structuring community, favoring the coexistence of species, especially those characteristics of littoral zone. In lakes Olhos dÁgua and Confins, low richness and high species dominance associated with high taxonomic distinctness indicate a process of competitive exclusion. Finally, lake Sumidouro, affected by periodic droughts and consequent population reductions, must have favoring of littoral and rapid growth species, resulting in zooplankton community dominated by Rotifera, a group with high richness and low evenness. It was observed that richness, evenness and diversity indices are influenced by factors associated to eutrophication, while taxonomic distinctness metrics are little influenced by environmental features.